Health Misinformation and the Power of Narrative Messaging in the Public Sphere - Caulfield, Timothy; Marcon, Alessandro R; Murdoch, Blake; Brown, Jasmine M; Perrault, Sarah Tinker; Jarry, Jonathan; Snyder, Jeremy; Anthony, Samantha J; Brooks, Stephanie; Master, Zubin; Rachul, Christen; Ogbogu, Ubaka; et al. (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2019)
Numerous social, economic and academic pressures can have a negative impact on representations of biomedical research. We review several of the forces playing an increasingly pernicious role in how health and science information is interpreted, shared and used, drawing discussions towards the role of narrative. In turn, we explore how aspects of narrative are used in different social contexts and communication environments, and present creative responses that may help counter the negative trends. As traditional methods of communication have in many ways failed the public, changes in approach are required, including the creative use of narratives.